Ответы и объяснения

2012-11-03T08:15:37+00:00

1/((y-1)(y-2)) + 1/((y-2)(y-3)) + 1/((y-3)(y-4)) = 3/((y-1)(y-4)),

1/((y-1)(y-2)) + 1/((y-2)(y-3)) + 1/((y-3)(y-4)) =

= ((y-3)(y-4)+(y-1)(y-4)+(y-1)(y-2))/((y-1)(y-2)(y-3)(y-4)) =

= ((y-4)(y-3+y-1)+(y-1)(y-2))/((y-1)(y-2)(y-3)(y-4)) =

= ((y-4)(2y-4)+(y-1)(y-2))/((y-1)(y-2)(y-3)(y-4)) =

= (2(y-4)(y-2)+(y-1)(y-2))/((y-1)(y-2)(y-3)(y-4)) =

= (y-2)(2(y-4)+y-1)/((y-1)(y-2)(y-3)(y-4)) =

= (2y-8+y-1)/((y-1)(y-3)(y-4)) =

= (3y-9)/((y-1)(y-3)(y-4)) =

= 3(y-3)/((y-1)(y-3)(y-4)) =

= 3 /((y-1)(y-4))